Pemanfaatan Limbah Minyak Jelantah Menjadi Lilin Aromaterapi di Desa Sarimukti - Agna Nisa Maghfira; Sofiy Khoirunnisa; Syifa Rahmah Purnama; Nazma Fathya Sutarjo; Rismayani Rismayani; Rezqya Aulia Azyuranie Muniroh; Rifawasilah Erwanda; Hanif Fajarudin; Yoan Yuniar Erlangga; Rendi Oktora; Indra Budi Jaya (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Used cooking oil cannot be reused due to its changed physical and chemical structure, or commonly referred to as “minyak jelantah”. Repeated use of minyak jelantah can pose a risk of various diseases. Meanwhile, “minyak jelantah” is included in waste that is difficult to decompose if it is just thrown away. The utilization of used cooking oil into candles is a solution to this problem. Based on research using observation methods in Sarimukti Village residents, and experimental research methods and documentation, minyak jelantah waste can be reduced by being utilized into aromatherapy candles. Based on the organoleptic test, the results show that the color is not suitable, while the shape and smell are suitable based on the concentration of stearic acid and telon oil added. Based on the burn time, the more telon oil added, the faster the candle runs out.